Virus-Like Particles as a Vaccine Delivery System: Myths and Facts - Roy, Polly (Pharmaceutical Biotechnology, 2009)
Vaccines against viral disease have traditionally relied on attenuated virus strains or inactivation of infectious virus. Subunit vaccines based on viral proteins expressed in heterologous systems have been effective for some pathogens, but have often suffered from poor immunogenicity due to incorrect protein folding or modification. In this chapter we focus on a specific class of viral subunit vaccine that mimics the overall structure of virus particles and thus preserves the native antigenic conformation of the immunogenic proteins. These virus-like particles (VLPs) have been produced for a wide range of taxonomically and structurally distinct viruses, and have unique advantages in terms of safety and immunogenicity over previous approaches. With new VLP vaccines for papillomavirus beginning to reach the market place we argue that this technology has now ‘come-of-age’ and must be considered a viable vaccine strategy.